2016
DOI: 10.13080/z-a.2016.103.012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tomato quality attributes using near infrared spectroscopy and reference analysis

Abstract: The research objective was determination of ripening attributes of intact tomato (Lycopersicon esculentum Mill.) cv. 'Rutuliai' using near infrared (NIR) spectroscopy and reference analysis. Tomatoes were picked at six different ripening stages in order to evaluate the correlation between data obtained by near infrared spectra and physicalchemical analyses and how the quality parameters change during ripening. Primarily, spectroscopic measurements were followed by chemical analyses. NIR spectroscopy measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…A coefficient of determination ( R 2 ) of 0.88 was achieved, but again the model was not tested on independent fruit populations. Most recently, Radzevicius et al [ 20 ] reported the use of the luggable NIR Case NCS001A (Sacmi Imola S.C., Italy) for estimation of tomato DM, SSC, and firmness, but calibration statistics were not presented.…”
Section: Introductionmentioning
confidence: 99%
“…A coefficient of determination ( R 2 ) of 0.88 was achieved, but again the model was not tested on independent fruit populations. Most recently, Radzevicius et al [ 20 ] reported the use of the luggable NIR Case NCS001A (Sacmi Imola S.C., Italy) for estimation of tomato DM, SSC, and firmness, but calibration statistics were not presented.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of total soluble protein were lower in immature green fruits compared to leaves, and declined further in all lines as ripening progressed ( Supplementary Figures S7 and S8 ). Gels for Fld detection were therefore loaded on the basis of FW, considering that unlike protein levels, the fraction of dry matter did not change significantly between tomato ripening stages (Matsuda and Kubota, 2010; Radzevičius et al, 2016). Figure 5A shows that mature-sized Fld was expressed in the green pericarp of immature Slpfld and Slcfld fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Impact of tomato hybrid (the factor B) and environment (weather conditions: the factor A: A1 = 2011, A2 = 2012, A3 = 2013) on dry matter content -DM ( The highest dry matter content was determined in 2013 in all hybrids, and the lowest in the year 2012 of research. The total dry matter content in various tomato genotypes varied from 4.0% to 7.5% of fruits fresh weight (RADZEVIĈIUS et al, 2016). In the three-year study the highest dry matter content was recorded in hybrid Rally compared to standard hybrid.…”
Section: Table 3 Year and Hybrid Effects On Dry Matter Content In Tementioning
confidence: 92%